Localization of right ventricular non-apical lead position: comparison of three-dimensional echocardiography, computed tomography, and fluoroscopic imaging. Issue 3 (March 2021) - Chen, Yung-Lung; Wang, Hui-Ting; Chen, Huang-Chung; Chai, Han-Tan; Lee, Yi‐Wei; Liu, Wen-Hao
Objective: Right ventricular (RV) septal pacing is considered a better pacing procedure compared with traditional apical pacing. This study aimed to investigate agreement among computed tomography (CT), three-dimensional echocardiography (3D-echo), and fluoroscopy for evaluating the tip of the RV pacing lead in the non-apical position in patients with permanent pacemaker implantation. Methods: Fifty-four patients were prospectively enrolled. Data on patients' characteristics and imaging findings were analyzed. The agreement rate in distinguishing the RV septal lead position among the three imaging modalities was determined. Results: Thirty-three (61%) patients were men and the median age was 76 years. Overall, the agreement rate among the three imaging modalities was 87% (47/54; Kappa ratio: 0.734). The agreement of 3D-echo compared with thoracic CT (Kappa ratio: 0.893) was better than that for thoracic CT and fluoroscopy (Kappa ratio: 0.658). Agreement between fluoroscopy and 3D-echo was lowest (Kappa ratio: 0.632). Conclusions: Agreement in evaluating the position of the septal lead between thoracic CT and 3D-echo is better than that between other imaging modalities. Our findings indicate that 3D-echo imaging might be the best imaging tool for defining the tip of the RV non-apical lead position and be useful for guiding positioning of the RV lead.